Comprehensive Meta-Analysis of Developmental Reading Interventions: Evaluating Effectiveness and Strategies for Improvement - Ismail, Hijril (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sulawesi Tenggara, 2024)
This meta-analysis evaluates the effectiveness of developmental reading interventions on literacy outcomes among children and adolescents, synthesizing data from 120 studies published between 2019 and 2023. The results demonstrate that these interventions exert a moderate to large positive impact, with phonics-based approaches emerging as the most effective, particularly in early childhood education. Fluency-building and comprehension strategies also play a significant role in enhancing reading proficiency, underscoring the necessity of a balanced instructional approach. The analysis further indicates that long-term interventions are more successful in achieving sustained literacy improvements, emphasizing the critical need for continuous support. Moreover, the substantial benefits observed among students from lower socio-economic backgrounds highlight the potential of these programs to mitigate educational disparities. While the promise of technology-enhanced interventions is acknowledged, their success hinges on factors such as accessibility and teacher readiness. These findings offer valuable direction for educators, policymakers, and researchers in designing and implementing effective reading interventions that promote literacy development across diverse student populations.